Factors Contributing to Work Fatigue Among Construction Workers - Fitri, Rika Yulianti; Sukesi, Tri Wahyuni; Hariyono, Widodo (ARTERI : Jurnal Ilmu Kesehatan, 2023)
The construction sector is one of the work sectors with a high level of risk of danger. The activities carried out by construction workers can cause errors and work accidents which are influenced by fatigue. This research aims to understand the factors related to work fatigue in construction workers in the Drinking Water Management System Project. The research method used was an explanatory study with a cross-sectional design, with a total sample of 30 people taken using a total sampling technique. Primary data was collected by distributing standard questionnaires, namely the Subjective Self Rating Test and Depression Anxiety Stress Scales (DASS) 42. Data were analyzed univariately using the frequency distribution test, bivariate analysis using the Chi-Square test, and data were visualized using the Tableau Public 2022 application. From the results, the research found that age (p=0.104), education (p=0.419), and length of work (p=0.063) were not related to work fatigue, while nutritional status (p=0.042) and work stress (p=0.028) were related to the incidence of work fatigue. The research conclusion is that nutritional status and work stress are related to work fatigue in construction workers in the Drinking Water Management System Project. Suggestions to project organizers, it is necessary to carry out effective stress management and coping for workers to reduce work fatigue and maintain workers' nutritional status by providing food according to workers' calorie needs.